PENGGUNAAN ALAT BUKTI DIGITAL DALAM KOMPUTER FORENSIK PADA PENYIDIKAN TINDAK PIDANA MAYANTARA DI DIREKTORAT KRIMINAL KHUSUS POLDA SUMBAR - Noffezar Noffezar; Fitriati Fitriati; Iyah Faniyah (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
Article 5 of Law No. 11 of 2008 concerning Electronic Information and Transactions states that electronic information and / or printed results from electronic information are valid evidence and have legal legal consequences. The use of digital evidence through computer forensics by investigators still encounters various problems. This research is legal research with analytical descriptive specifications. The form of print out of electronic evidence is contained in the minutes of investigation. Without going through Digital Forensics, an electronic document cannot be used as evidence because the validity of the electronic document cannot be guaranteed. In the investigation process physical evidence and digital evidence are part of a complementary investigation process. Constraints on the use of digital evidence on computer forensics are the few people who can be asked to become expert witnesses. The absence of a forensic computer laboratory at the West Sumatra Regional Police. Digital proofing is carried out by experts. Efforts are being made to overcome the obstacles in proof using digital evidence with computer forensics, among others, by using information or opinions from telematics experts who have expertise in their fields.